Strong Education and Strong Family as the Premise to Sound Grooming in the Novels of Jane Austen and Louisa May Alcott - Goswami, Renu; Kumaran, Dr. Ritu (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: For the young adolescent girls, the home was a model of feminine values, morals and ideals that they imbibed by observing and understanding the separate gender-based roles and responsibilities of their parents. Conformity to social norms distinguished an angelic woman from a fallen woman. In the nineteenth century Victorian Era, child grooming and rearing was different from its predecessors depending on the differences in classes. This paper compares Jane Austen’s Sense and Sensibility with Louisa May Alcott’s Rose in Bloom particularly their female protagonists to highlight the role of family in instructing, guiding and mentoring their children in order to be socially agreeable. In addition, this paper alludes to John Locke’s philosophy on the education of children, psychological theories and Maslow’s theory of motivation. In the absence of a formal education, parents, siblings and the family circles contributed significantly to the overall development of young maidens.